2014
DOI: 10.1161/atvbaha.113.302131
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein–Coupled Receptor 91 and Succinate Are Key Contributors in Neonatal Postcerebral Hypoxia-Ischemia Recovery

Abstract: Objective-Prompt post-hypoxia-ischemia (HI) revascularization has been suggested to improve outcome in adults and newborn subjects. Other than hypoxia-inducible factor, sensors of metabolic demand remain largely unknown. During HI, anaerobic respiration is arrested resulting in accumulation of carbohydrate metabolic intermediates. As such succinate readily increases, exerting its biological effects via a specific receptor, G-protein-coupled receptor (GPR) 91. We postulate that succinate/GPR91 enhances post-HI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 61 publications
4
51
1
6
Order By: Relevance
“…The data using endothelial specific gene targeting in the paper supports, however, that the EP4 receptor has an important vascular role regulating cerebral perfusion in HI. The results agree with a recent publication demonstrating that the EP4 receptor in the immature brain is also critical for angiogenesis after HI (Hamel et al, 2014). Indeed, the article highlights the importance of the vascular bed in neonatal HI and brings attention to it as an attractive therapeutic target for CNS protection (Xing et al, 2012).…”
supporting
confidence: 90%
“…The data using endothelial specific gene targeting in the paper supports, however, that the EP4 receptor has an important vascular role regulating cerebral perfusion in HI. The results agree with a recent publication demonstrating that the EP4 receptor in the immature brain is also critical for angiogenesis after HI (Hamel et al, 2014). Indeed, the article highlights the importance of the vascular bed in neonatal HI and brings attention to it as an attractive therapeutic target for CNS protection (Xing et al, 2012).…”
supporting
confidence: 90%
“…In contrast, high levels of succinate after cerebral 1R1 enhance brain vascularization and recovery by inducing expression of VEGF through SUCNR1, which is mainly expressed in neurons and astrocytes (Hamel et al, 2014). In RGC and rat cerebral astrocyte neuronal cell line (RPA), SUCNR1 upregulates VEGF via PGE 2 and prostaglandin E receptor 4 (EP 4 ), already known to promote angiogenesis (Hamel et al, 2014).…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%
“…In RGC and rat cerebral astrocyte neuronal cell line (RPA), SUCNR1 upregulates VEGF via PGE 2 and prostaglandin E receptor 4 (EP 4 ), already known to promote angiogenesis (Hamel et al, 2014). Since succinate only transiently accumulates in case of brain 1R1, long-acting agonists of SUCNR1 might potentiate the recovery process (Hamel et al, 2014).…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Recent studies have elucidated the role succinate in murine models of cerebral hypoxia-ischemia revascularization and diabetic retinopathy. 48, 49 Using GPR91-deficient mice, Hamel et al 48 demonstrated increased succinate levels in close proximity to brain infarcts, and GPR91 enhanced microvascular density and reduced infarct size. The effect of succinate on VEGF release was mediated by GPR91 and prostaglandin E 2 (PGE 2 ).…”
Section: Metabolic Flexibility and Dysfunction In Endothelial Cellsmentioning
confidence: 99%